Basque Immigrants and Nevada's Sheep Industry : Geopolitics and the Making of an Agricultural Workforce, 1880-1954 - Saitua, Iker, 1987- (Book collections on Project MUSE., 2019)
"This book contributes to a wider understanding of the significance of the Basque immigration in the western sheep industry with a historically refreshed perspective. It contributes to the existing new historiography of the American West by looking more critically at the Basque immigrant experience in the open-range sheep industry of Nevada. It deconstructs the essentialist view that attributed to Basques special sheepherding skills by exploring this immigrant experience within its economic, social, cultural, political, and international context. This book is targeted to an academic, student and wider audience interested in the Modern American West and Basque Studies."--Provided by publisher.